A review of research trends in order batching, sequencing and picker routing problems (2018)
This paper provides a discussion about order batching, sequencing and picker routing problems in order to identify research trends and gaps to meet real conditions of warehouses operations. Main approaches to order picking operations, problem settings, function objectives, and solution methods implemented in the literature are exposed. The future research trends focus on the importance of considering due dates, multiobjective approaches, dynamic arrivals of customer orders, multiple pickers, congestion and picker blocking, and 3D warehouse layouts with multiple blocks. © 2018.